2019
DOI: 10.1002/micr.30530
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis is associated with complications after microvascular surgery: An NSQIP data analysis

Abstract: Background Complications after microvascular surgery, such as partial flap loss, and arterial/venous compromise cannot only increase morbidity for the patient but also tax the healthcare system. Thrombocytosis, both essential and reactive, can predispose patients to thrombosis and hemorrhage and thus should intuitively have an effect on the outcome of microvascular free tissue transfers. We sought to evaluate the effect of preoperative thrombocytosis on outcomes after microvascular free flap surgery. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…In a large study not specific to the head and neck, premorbid thrombocytosis in patients undergoing free tissue transfer not only prolonged their hospital stay but was associated with increased rates of postoperative complications and immediate revision surgery unrelated to flap vitality. 16 Platelet aggregation is necessary to activate the coagulation cascade, the end product of which is thrombosis, a known and important contributor to early free flap failure. 4,8,9 The role of thrombolytics to promote overall flap health and survival is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study not specific to the head and neck, premorbid thrombocytosis in patients undergoing free tissue transfer not only prolonged their hospital stay but was associated with increased rates of postoperative complications and immediate revision surgery unrelated to flap vitality. 16 Platelet aggregation is necessary to activate the coagulation cascade, the end product of which is thrombosis, a known and important contributor to early free flap failure. 4,8,9 The role of thrombolytics to promote overall flap health and survival is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, POTCT has been used as a reliable marker of complications in urologic and colorectal surgery 7–9 . Similarly, preoperative thrombocytosis has also been used as a marker to predict postoperative complications, possibly due to underlying inflammatory responses that can inhibit wound‐healing 11–13 …”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, Tarabishy et al reported an increased risk for blood transfusion in patients with preoperative thrombocytosis (> 450,000/μL). 12 Therefore, based on available evidence and a lack of literature on the current population, we recommend PLT levels to be maintained above the lower limit of normal and below 361,000/μL with a goal of approximately 200,000/ μL to optimize postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%